2020
DOI: 10.2174/1871530319666191023141638
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Attenuates the Development of TGF-β1- Induced EndMT through Down-regulating the Notch Signaling

Abstract: Background and objective: Endothelial-mesenchymal transition (EndMT) not only occurs during embryonic development, but also contributes to various diseases including cardiovascular diseases, fibrosis, and even cancer. However, the specific molecular biological mechanism and relationship of related pathways have not been fully elucidated. This study aims to explore the inhibitory effect of HGF on EndMT and the molecular mechanism of Notch signal in this process. Methods: HUVECs were treated with TGF-β1 and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Moreover, TGF-β signaling exerts its effects by interacting with other signaling cascades, including Wnt and Notch (Fig. 5a, c) [267][268][269].…”
Section: Endothelial-mesenchymal Transition (Endmt)mentioning
confidence: 99%
“…Moreover, TGF-β signaling exerts its effects by interacting with other signaling cascades, including Wnt and Notch (Fig. 5a, c) [267][268][269].…”
Section: Endothelial-mesenchymal Transition (Endmt)mentioning
confidence: 99%
“…In addition, even if not directly investigated in SSc, hepatocyte growth factor and the aldosterone receptor-blocker spironolactone were found to prevent TGF-β1-induced EndoMT in human umbilical vein ECs [ 119 , 149 , 150 ]. Finally, TGF-β1-induced EndoMT was reverted after treatment with triazole arginylglycylaspartic acid antagonist in endothelial precursor cells [ 151 ].…”
Section: Main Molecular Pathways Driving Myofibroblast Differentiation From Vascular Wall Residing Cells In Systemic Sclerosis and Relatementioning
confidence: 99%
“…Increasing evidence demonstrates that EndMT is vital for production of myofibroblasts in fibrotic tissues or organs ( Zeisberg et al, 2007 ; Potenta et al, 2008 ; Zeisberg et al, 2008 ; Li et al, 2009 ). It has been reported that TGF-β can act as an upstream modulator in stimulation of EndMT ( Hou et al, 2019 ; Yang et al, 2019b ). The enhanced expression of TGF-β1 induces an increase in inflammatory factors and asymmetric dimethylarginine (ADMA), whereas a decrease occurs in Nrf2, dimethyl arginine dimethylaminohydrolase-1 (DDAH1), VE-cadherin, secretion of nitric oxide (NO) and activity of nitric oxide synthase (NOS).…”
Section: Curcumin and Transforming Growth Factor-beta In Different DImentioning
confidence: 99%